2005
DOI: 10.1016/j.foodcont.2003.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Listeria spp. in domestic refrigerators in Portugal

Abstract: The main objectives of this study were to determine the incidence of Listeria spp. in Portuguese domestic refrigerators and to evaluate some of the hygienic practices in the domestic environment that might contribute to the persistence of the organisms. It was found that L. monocytogenes was present in 3 domestic refrigerators of the 86 investigated. L. grayi and L. innocua were also isolated from 4 and 1 refrigerators, respectively.Overall, the information obtained from our survey demonstrates the need for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 15 publications
1
54
1
1
Order By: Relevance
“…Means followed by the same lowercase letter in the same row for the same bacterium are not significantly different (P Ͼ 0.05). at low temperatures, particularly L. monocytogenes, which is one of the major foodborne pathogens known to grow under refrigeration (25). For inactivating these bacteria, DUV-LEDs may therefore be more appropriate than LP lamps.…”
Section: Discussionmentioning
confidence: 99%
“…Means followed by the same lowercase letter in the same row for the same bacterium are not significantly different (P Ͼ 0.05). at low temperatures, particularly L. monocytogenes, which is one of the major foodborne pathogens known to grow under refrigeration (25). For inactivating these bacteria, DUV-LEDs may therefore be more appropriate than LP lamps.…”
Section: Discussionmentioning
confidence: 99%
“…Acremonium was also commonly found in meat storage refrigerators (40.0%). Airborne Cladosporium and Acremonium have been isolated from meat processing areas (33,43), indoors (9), and other food processing areas (23).…”
Section: Aspergillus Ochraceus Is Associated With Balkan Endemicmentioning
confidence: 99%
“…(45). According to several studies on refrigeration temperatures, a wide percentage of retail and home refrigerators show temperatures above 4°C, a temperature that prevents most microbial growth and is recommended by many ready-to-eat food producers (9,11,12,20). Similarly, WHO (46) recommended the storage temperature of foods at a maximum of 5 °C in refrigerator.…”
Section: Aspergillus Ochraceus Is Associated With Balkan Endemicmentioning
confidence: 99%
“…The refrigerators operated above 5.0ºC during 58% of the test, nevertheless representing a reduction of 2.0ºC compared to a similar study done two decades earlier. In fact, there are benefits in terms of storage live extend and consequently in food waste reduction reducing storage temperature of the refrigerator to 4ºC and promoting home freezing [6]- [8]. In an experimental study making use of temperature loggers placed at three shelf levels of 119 domestic refrigerators it was found that most users open the door around 20 times per day [9].…”
Section: Introductionmentioning
confidence: 99%